The Moderating Effects of Personal Resources on Caregiver Burden in Carers of Alzheimer's Patients - Sołtys, Anna; Bidzan, Mariola; Tyburski, Ernest (Frontiers in Psychiatry, 2021)
Caring for persons with Alzheimer's disease can be an extremely difficult experience. To date, there has been a lack of research into the role of intermediary variables in the relationship between caregiver personality and psychosocial functioning. The growing numbers of dementia patients worldwide mean that more people are involved in their care, making research into this area a pressing concern. Both a caregiver’s personality and personal resources play a key role in their capacity to cope with stressful situations. In order to determine how personal resources moderate the relationship between personality and burden of care, a total of 100 caregivers of Alzheimer's patients (78 women and 22 men) were asked to complete a set of questionnaires to assess personality, personal resources (sense of coherence, generalized self-efficacy, and perceived social support), as well as their levels of stress, depression, and commitment to care. Structural equation modeling and latent growth analysis suggest that personal resources explain the mechanisms underlying burden of care and moderate its relationship with per-sonality. Our findings indicate that personal resources are a critical predictor of burden of care. Therefore, caregivers must be provided with appropriate support, taking into account their resources and personality profiles.